Constitutional Courts in the German States - Reutter, Werner. author. aut Link
XVI, 148 p. 6 illus.
Keywords: The book takes stock on constitutional adjudication in the German states. It includes surveys on the Constitutional Court in Berlin, the origins and development of state constitutional courts in Germany, their status and mode of operation, their justices, and the role these courts play at the subnational level in Germany.